Young children's cognitive development : interrelationships among executive functioning, working memory, verbal ability, and theory of mind - Schneider, Wolfgang, 1950 June 19-; Schumann-Hengsteler, Ruth, 1957-; Sodian, Beate, 1956- (L. Erlbaum Associates, 2005)
A critical part of early childhood development is the development of "theory of mind" (ToM), which is the ability to take the perspective of another person. The main purpose of this book is to discuss and integrate findings from prominent research areas in developmental psychology that are typically studied in isolation, but are clearly related.